Kalimat Metaforis Sebagai Sarana Estetika dalam Lirik Lagu nDangdut - Muhamad Hermintoyo (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
Abstract In providing an aesthetic element, the lyricist will express it through poetic diction. In the hands of creative lyric writers, a figurative language will emerge. Metaphorical lyrics understanding does not have to have the same meaning that is written. Poetic language / poetic lyrics, the words can mean the meaning depends on the listener's understanding. Even so in the song nDangdut. In general, the song Dangdut tends to have a theme of love compared to other themes. This article discusses metaphorical diction as an aesthetic means. Meaning of metaphorical diction using hermeneutical reading. Keywords: diction, metaphor, hermeunetic, lyrics, dangdut